Myocardial iron is strongly associated with reproductive function in beta-thalassemic women under chelation therapy - M. A. Castaldi; C. Fulgione; L. Marino; S. G. Castaldi; L. Giugliano; C. Selleri; M. Guida; V. Frega; L. Cobellis; A. Filosa; M. Casale (IMR Press, 2020)
Objective: To evaluate gynaecological features of a group of transfusion dependent beta-thalassemic women and to analyze their reproductive function with the morpho-functional features of genital female tract. Materials and Methods: Cross-sectional study in a University Hospital and Tertiary Care Center. Fifty-nine transfusion-dependent beta-thalassemic women in reproductive age, were divided into two groups: to group A were assigned women with spontaneous menarche (n=44), while to group B were allocated patients with inducted menarche. Data on demographic characteristics, iron overload in liver and heart (evaluated with T2* RMN method), chelation therapy, and reproductive function were collected. Difference in demographic characteristics, chelation therapy, iron status, and reproductive function between groups were assessed, together with correlation analysis of iron overload. Results: Patients in group B had a worse reproductive function and a higher myocardial iron overload, than patients in group A. Moreover multivariate logistic regression showed a significant correlation between uterine biometry, FSH, E2, parity and hearth iron T2*HSIV, but not with liver iron. Conclusion: The present data shows that myocardial iron loading could be putative of prolonged and severe iron overload in the female genital tract, impairing fertility and reproductive function in patients affected with beta-thalassemia major under chelation therapy.